2014
DOI: 10.1016/j.coi.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid presentation by human CD1 molecules and the diverse T cell populations that respond to them

Abstract: CD1 molecules bind and present lipid-based antigens to T cells. Humans express both Group 1 (CD1a, CD1b and CD1c) and Group 2 (CD1d) CD1 molecules with nonredundant functions in the human immune response. Studies of Group 1 CD1 molecules and the T cells that respond to them have lagged behind Group 2 due to the lack of a suitable model system. However, recent work has thrust the Group 1 CD1s into the limelight, revealing their importance in tissue surveillance and microbial defense. Here I review recent advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…Uldrich et al demonstrated reactivity to the microbial lipid α-GalCer, and even though the affinity and reactivity to this lipid was much less than that observed in the case of iNKT cells (16 μM compared to 0.5 μM, and evidenced by lower tetramer staining intensity to Vδ1 cells than iNKT cells), it sets an important precedent that microbial lipids may be stimulatory. Directly relevant to sulfatide reactivity, some pathogens, such as Trypanosoma cruzi [42] and Mycobacterium tuberculosis [43], can produce sulfatide-like compounds, and it is also likely that other bacterial species and stressed cells make antigens that can be presented by CD1 molecules to these γδ T cells ([44] and reviewed in [45]).…”
Section: Towards a More Global Understanding Of γδ T Cell Activationmentioning
confidence: 99%
“…Uldrich et al demonstrated reactivity to the microbial lipid α-GalCer, and even though the affinity and reactivity to this lipid was much less than that observed in the case of iNKT cells (16 μM compared to 0.5 μM, and evidenced by lower tetramer staining intensity to Vδ1 cells than iNKT cells), it sets an important precedent that microbial lipids may be stimulatory. Directly relevant to sulfatide reactivity, some pathogens, such as Trypanosoma cruzi [42] and Mycobacterium tuberculosis [43], can produce sulfatide-like compounds, and it is also likely that other bacterial species and stressed cells make antigens that can be presented by CD1 molecules to these γδ T cells ([44] and reviewed in [45]).…”
Section: Towards a More Global Understanding Of γδ T Cell Activationmentioning
confidence: 99%
“…Human CD1a, CD1b, and CD1c molecules are members of group I and group II is formed by CD1d. CD1a-c molecules are expressed in professional antigen-presenting cells (APCs) and are involved in the defense against microbial infections, like mycobacteria [2]. CD1d is also expressed on professional APCs including dendritic cells (DCs), macrophages (Mϕ), monocytes, and some B cells.…”
Section: Introductionmentioning
confidence: 99%
“…21 Therefore, 3 processing and presentation mechanisms have been characterized: (1) the exogenous (or endosomal) pathway, where antigenic peptides are generated and coupled to MHC-II molecules in phagolysosomes and then transported to the cell surface and presented to CD4 1 T cells; (2) the endogenous (or proteasome) pathway, where the intracellular proteins are degraded by the proteasome, and the resulting peptides are coupled to MHC-I molecules in the Golgi and then transported to plasma membrane and presented to CD8 1 T cells; and (3) mechanisms where lipid antigens are coupled to CD1 family molecules and presented to CD8 1 T cells, g/d T cells, or NK T cells. 22 Exogenous antigens can also be presented to CD8 1 T cells via MHC-I complexes, a process termed crosspresentation. In cross-presentation, internalized proteins are retrotranslocated into the cytosol and degraded by the proteasome.…”
Section: Q10mentioning
confidence: 99%